Thoracic Wall Reconstruction for Primary Malignancies in Children: Short- and Long-term Results - Dingemann, C.; Linderkamp, C.; Weidemann, J.; Bataineh, Z.A.; Ure, B.; Nustede, R. (European Journal of Pediatric Surgery, 2012)
Aim Primary thoracic wall malignancy is a rare and diverse entity in children. Surgical treatment commonly involves major chest wall resection causing large defects requiring complex reconstruction. In adults, the use of alloplastic and/or xenogenic materials and muscle flap repair is well established. However, literature provides only little information on procedures in children. We report our experience in 8 consecutive children who underwent chest wall resection and reconstruction with regard to surgical treatment and outcome.Patients and Methods Retrospective study of all children with primary malignant chest wall tumors requiring rib resection and reconstruction with prosthetic material performed in our institution between November 2002 and April 2010. Endpoints were postoperative complications and long-term results, focusing on scoliosis defined radiologically by the Cobb angle.Results 8 children (7 male, 1 female) with a median age of 10.6 (4.1–18.9) years underwent resection of thoracic wall tumors. A mean number of 3 (1–5) ribs were resected. Stability was obtained using rigid prosthetic material (STRATOS™ titanium bar) in 2 patients and/or non-rigid prosthetic material (Goretex® patch in 6 patients, Vicryl® patch in 3 patients, Tutopatch® in 1 patient). A muscular flap was added in 5 patients. Postoperative complications included superficial wound infection (n = 2) and dislocation of a titanium bar necessitating removal in 1 patient. No infections of the prosthetic material were observed. No perioperative mortality occurred. At a mean follow-up of 37.5 (4–97) months, 6 patients were alive. 2 patients died due to early tumor recurrence. Mild scoliosis (Cobb angle 10–20°) was detected in 2 of the surviving patients (33%).Conclusion Surgical reconstruction after resection of malignant thoracic wall tumors using non-rigid prosthetic material is safe and effective in pediatric patients, whereas rigid prosthetic material might dislocate. Scoliosis represents a long-term complication after chest wall reconstruction and should be monitored during routine follow-up.
Keywords: primary malignant thoracic wall tumor; reconstruction; prosthetic material; children; outcome